RANCANG BANGUN KOMPRESOR MINI DENGAN MENGGUNAKAN TABUNG FREON MOTOR INDUKSI AC - Antu, Evi Sunarti; Botutihe, Sjahril (Universitas Bina Taruna Gorontalo, 2023)
This study aims to find out how the components of the material are used in designing a mini compressor building using an AC induction motor freon tube, knowing how the benefits of an AC induction motor freon tube and knowing how to design a mini compressor using an AC induction motor freon tube. This product research and development model is carried out using development research or often referred to as Research and Development (R & D). Research and development (research and development) aims to produce new products through the development process. The main material used in this research is waste from AC freon tubes. Tool testing was carried out 3 times to get the best time to fill the compressor wind tube. From the test results, it was found that the maximum pressure of 120 Psi was obtained at 15 minutes of filling.